Espaço de educação superior da América Latina e Caribe: pontos e estratégias predominantes para sua constituição - Castilho, Katlin Cristina de (2020)
In this study, we analyzed the predominant points and strategies for the construction and management of the Higher Education Area of ​​Latin America and the Caribbean (EESALC), from the specialized literature on subjects and lectures by Brazilian university professors, students involved in actions and referrals accordingly. Used as a methodological basis or historical-dialectical material (MARX, 1985, 2004, 2007, 2011; LUKÁCS, 1979; LIMA, 2003; PAULO NETTO, 2011), we visualize exhibiting a tension between variables and contradictions in production relations, such as are imperative in reading the object. This study had as a starting point a discussion on a theme via the state of knowledge of the investigation and had questionnaires as instruments of data collection that were applied to university professors at UNICAMP and UFMG (in a total of 24 participants) are part of the pilot plan of the ongoing LAC integration process, called the Latin American and Caribbean Higher Education Space (ENLACES). As the feedback points point out the central points for the construction and consolidation of the Higher Education Area of ​​Latin America and the Caribbean (EESALC), from the respondents' statements were: 1) actions to establish proximity standards between the region's HEIs; 2) establishment of integration mechanisms based on the consolidation of common objects and actions, and 3) financing and financial resources. The strategies or measures for consolidation highlighted were: a) creation of a structure for credit equivalence and common disciplines for the bloc; b) academic mobility planning; c) promote the reduction of bureaucracies in the validation of the block's titles; d) design a curricular structure that includes all States involved in the block; e) provide resources and referrals to strengthen internationalization; among others. The study made it possible for us to realize that the construction and consolidation of the Latin American and Caribbean Higher Education Area is possible and could expand university relations and partnerships between partner governments, however, it is necessary to engage in more directive and planned dialogues for their achievement.